EFFICIENCY IMPROVEMENT CHALLENGES OF LAW APPLICATION IN UKRAINE - Obikhod, Tatiana; Bilenchuk, Petro (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to study the effectiveness of rule-making and law application in the conditions of the formation and development of market relations in Ukraine, when the need for reforms in different areas of life is a key necessity. The methodological base of an investigation is connected with historical legal, dialectical and special methods of cognition. Results: the step-by-step implementation of the law in public life is considered and the need for a comprehensive knowledge of the political, economic and spiritual components for the effective implementation of the law norm is emphasized. Authors proposed effective methods of rule-making activities such as experimental legislation, graphic representation and strict control with strict sanctions. Discussion: to search for methods of overcoming legal nihilism in Ukraine and to consolidate the norm as an essential link in public life.